(untitled) (GEOAREA | Jurnal Geografi, 2026)
Indonesia boasts a rich and diverse array of natural tourist attractions, one of which is Curug Tilu, located in Cipelah Village, Rancabali Subdistrict, Bandung Regency. This area offers the charm of three waterfall streams, cool mountain air, and a pristine natural environment. Since its official opening in 2017, the area has continued to undergo development. This study aims to examine the geographical conditions of Curug Tilu’s tourist attractions, its development strategies, and the challenges it faces. The study employs a descriptive qualitative method with a field study approach. Data were collected through observation, interviews, documentation, and literature review from 35 informants, including tourism managers, village officials, and visitors. The results show that the development of this tourist attraction is carried out through digital promotion, the construction of tourism infrastructure, and the involvement of the local community in its management. However, there are several challenges, such as limited funding, suboptimal road access, promotional efforts that do not sufficiently reach audiences outside the region, and seasonal challenges such as a decrease in water flow during the dry season. In conclusion, geographically, Curug Tilu has the potential to become a premier natural tourist destination if managed professionally and sustainably.